A New Color Image Watermarking Scheme - Verma, Bhupendra (2006)
A new spatial domain probability based watermarking scheme for color Images is proposed. The blue channel of the color image has been used for watermark embedding. Host image is divided into 8x8 blocks and each bit of the binary encoded watermark is embedded in each such block. For each inserted bit, intensity of all the pixels in the block is modified according to the embedding algorithm. Non-blind probability based watermark extraction is performed with the help of original host image. The method has been proved to be robust to various image processing operations such as filtering, lossy image compression, and various geometrical attack such as rotation, scaling, cropping.